Optimalisasi Keterampilan Guru Bahasa Inggris Dan Bahasa Indonesia Merancang Dan Menerapkan Asesmen Autentik Di SMP Blora - Agnisa Widayanti; Gayatria Oktalina (Impact: Jurnal Pengabdian kepada Masyarakat, 2025)
Authentic assessment is an assessment approach that emphasises the link between learning activities and the real-world context. In implementing the Merdeka Curriculum, teachers are required to have the skills to design assessments that not only measure cognitive aspects, but also develop students' characters and competencies. This study aims to optimise the skills of Indonesian and English teachers at SMP Al Muhammad Cepu in designing and implementing authentic assessments. This study used a descriptive qualitative approach with a collaborative action research model. The informants in this study consisted of Indonesian and English teachers as the main subjects, as well as principals and students as supporting data. The research process was carried out through four stages, namely planning, implementation, observation-evaluation, and reflection. The results showed an increase in teachers' ability to develop learning tools based on authentic assessments, such as project assessments, portfolios, contextual assignments, and performance assessments. Teachers also showed improvement in providing descriptive feedback and reflecting on assessment practices. Although some performance assessments were not fully implemented due to time constraints and student readiness, overall the implementation of authentic assessments improved significantly. This study shows that a collaborative and reflective approach is effective in developing teachers' professional competence in implementing authentic assessment at the junior secondary school level.